Estudio de prefactibilidad para la implementación de una planta productora de aceite de sacha inchi (plukenetia volubilis) extra virgen - Vásquez Sologuren, Alonso (2015)
The following project is looking to implement a SacEl presente proyecto busca implementar una planta procesadora de aceite de sacha inchi. El objetivo principal de toda la investigación es demostrar la factibilidad del proyecto, estudiando la viabilidad de mercado, la viabilidad tecnológica y la viabilidad económica-financiera, todo bajo parámetros de impacto social positivos.ha Inchi oil processing factory. The main objective of the investigation is to demonstrate the feasibility of the project by studying the market, technology and financial viability under positive impacts on social environment. The product is searching to reach the market by its natural characteristics, free of any chemical supply in its production process, content of vitamins, minerals, nutrients and unsaturated fatty acids like Omega-3 (48,6%), Omega-6 (36,8%) and Omega-9 (8,3%); and its benefits like the improvement of systems in human body (like nervous, immune, digestive and osseous), the reductions of cardiovascular problems which make it better than other fatty acids oils.